THE INFLUENCE OF WORK DISCIPLINE AND CAREER DEVELOPMENT TO THE EMPLOYEE PERFORMANCE AT THE BPJS KETENAGAKERJAAN BRANCH OFFICE NORTH SULAWESI - Singal, Finny Suzana; Untu, Victoria (Universitas Sam Ratulangi, 2015)
Every organization, whether private and governmental one, is oriented to long-term goals, namely the development of the organization and will try to improveits performance in order to achieve the vision and mission of the company. The purpose of this research was to determine influence of employees’ discipline and career development to the employee performance at the BPJS Ketenagakerjaan branch office North Sulawesi. This research used an associative method with the aim to see the relationship between variables. Data were analyzed using multiple linear regression and saturated sampling techniques is used to collect 35 sample employees. The results showed the discipline of work and career development, have a significanly simultaneous effect on the employees performance. Labor discipline shows no significance, whereas caeer development is significantly influence employce performance. Leaders BPJS Ketenagakerjaan north sulawesi branch offices, would have to put more attention to the employees’ discipline since it will affect the employees’ performance. Keywords: work discipline, career development and employee performance